Dylematy i ograniczenia podmiotowości menedżerów pracujących w firmach międzynarodowych działających na terenie województwa lubuskiego = Dillemas and limitations of managers` subjectivity who work in international companies operating in Lubuskie Voivodship - Zygadło, Andrzej; Bednarczyk, Henryk (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The management of a company involves a sense of agency and autonomy, but it is also burdened with numerous costs and renunciations. Analyzed research results enabled the construction of a typology which was based on the way of coping with a conflict: personal life - professional life.
Keywords: menedżerowie; firma międzynarodowa; życie zawodowe; życie prywatne; województwo lubuskie